KARAKTERISTIK PEDAGANG ETNIK TIONGHOA DALAM MENGAKSES BANK SYARIAH - GAFUR, ABDUL (At-Taradhi Jurnal Studi Ekonomi, 2013)
The Chinese merchants interest in using the service of the Syariah banks is the interesting phenomena to observe. Using the quantitative-descriptive research methodology, this writing is the result of the research in the Chinese characteristics in using the service of the Syariah banks. The characteristics are such as their character based on their demography, their access to banking, their information sources in accessing the Syariah banks, the terms and the reasons why they use the service of the Syariah banks, and the information about their understanding toward the Syariah banks product terms. With this acknowledgement, it is hoped that the result of this writing will help the development of the Syariah banks in the future.